Avaliação de diferentes complexos de ferro e oxidantes para a degradação da mistura de fipronil, oxibenzona e propilparabeno em efluente sanitário terciário sob radiação solar - Marson, Eduardo Oliveira (2023)
Water and sewage treatment plants, which employ classical processes, were not designed to remove contaminants of emerging concern. Thus, the solar photo-Fenton process was evaluated as an alternative complementary treatment to those applied in a sewage treatment plant, for the simultaneous degradation of organic compounds fipronil, oxybenzone and propylparaben, added to the effluent in order to reach a concentration of 100 µg L–1 of each. The ligands ethylenediaminetetraacetic acid (EDTA) and ethylenediamine-N,N’-dissuccinic acid (EDDS) were assessed for the process application at pH 7.4 (natural of the matrix). Initially, for each ligand, the best experimental condition of the operational parameters (iron concentration, iron/ligand molar ratio (Fe:L) and H2O2 concentration) was determined. For FeEDTA, applying 100 µmol L–1 of iron in a Fe:L molar ratio of 1:1 and using 5.9 mmol L–1 of H2O2, 97% of mixture degradation was obtained after 65 min of treatment. Although the best iron concentration for both ligands was 100 µmol L–1, the FeEDDS complex required a higher Fe:L molar ratio (1:3) and a lower H2O2 concentration (1.5 mmol L–1), reaching 88% average mixture degradation after 99 min of radiation. Under the best conditions found for iron concentration and Fe:L molar ratio for both iron complexes, the persulfate and peroxymonosulfate application in the modified solar photo-Fenton process were evaluated. For the evaluated persulfate concentrations, average degradations of the mixture between 20% and 40% were obtained after the end of the process. This is because the sulfate radical reacts preferentially with target compounds with high electronic density, also suffering interference from the inorganic anions present in the effluent. For peroxymonosulfate, only for 5.9 mmol L–1, it was possible to obtain 95% of average degradation of the mixture for FeEDDS after 67 min of irradiation and 96% for FeEDTA after 14 min of radiation. However, at this peroxymonosulfate concentration, there was a reduction in the reaction medium pH. For the best oxidant (H2O2), bioassays and process cost estimates were performed. Bioassays with the fly Drosophila melanogaster showed that the toxicity of the untreated solution is due to the presence of fipronil, which was reduced after application of the modified solar photo-Fenton process using both complexes. Costs on a laboratory scale, in turn, suggested the FeEDTA complex as the most economically viable option for a real application, due to the high cost of the EDDS ligand.